(untitled) (MAUSAM, 1960)
Best (1953) has shown from an analysis of data from Geophys. Mem., No, 84 (Simpson 1949) that consideration of the drop size distribution in rain leads to the non-linearity of the relation between rain current (total charge brought down by rain per sq. cm per second) and rate of rainfall the purpose of the present paper is to show the same conclusions as reached by Best but with some slight modifications. It IS shown that a knowledge of rain current is also necessary to find out the variation in drop size distribution between two rain measurements, especially when both the liquid water content and intensity of rainfall are same in both cases. Further the origin of rain whether from freezing or non-freezing clouds, can be clearly brought out from a knowledge of the electric charge carried by rain. The difference in the electricity carried by precipitation with and without point discharge has been shown.